The Performance of Reit in Five Selected Asia Pacific Countries - Yeo, Ignatius Lip Khai (2013)
Real Estate Investment Trust (REIT) has been in the market since it was first developed in the US in the 1960s. REITs in Asia Pacific, with the exception of Australia, however did not take off until the beginning of the twenty first century. The emergence of this new asset class in the region received much attention from investors due to their unique characteristics and performance.The purpose of this paper is to determine the relationship of between the returns of Asia Pacific REITs and those of other assets, namely large cap stocks, small cap stocks, fixed income securities and unsecuritized real estate. This paper also aims to fill the research gap of the performance of Asia Pacific REITs before, during and after the global financial crisis of 2008. Findings have shown that the correlation between REITs performance and the other financial assets vary not only across countries but also differ during different economic cycles. As an asset class of its own they provide diversification benefits when held in a multi-asset portfolio. Investors are however required to readjust the portfolios due to the time-varying nature of the correlation between assets. Our study has also concluded that while the global financial crisis affects all asset classes, some assets are able to weather the impact better than others. REIT performances in some countries are also more resilient than others and recover faster from an economic downturn. We understand that due to geographical and market policy reasons different countries tend to use different approaches for their REIT regimes. While no one regime is made to suit all countries, the same policies can be applied to a certain extent. Full regime policies for individual countries would require tedious studies by regulatory bodies with in dept knowledge of the factors that affect REIT performance in the different countries.